Labelling black male genitalia and the 'new racism': the discursive construction of sexual racism by a group of Southern African college students. (18th November 2014) - Makoni, Busi
Abstract : This article explores the discursive construction of sexual racism through names assigned to the black penis by black male college students in Southern Africa. This analysis reveals use of three frequently occurring metaphors: zoomorphs, weapons and heroic historical figures. Collectively, these frequently occurring metaphors associate Southern African black men with notions of (i) wild, animalistic sexuality, (ii) dangerous, violent behaviour, and (iii) large sexual organs, which were prevalent racist ideologies of black male bodies during the colonial period. In addition, perceptions of sociocultural power dynamics attributed to patriarchy are foregrounded through metaphors related to royalty, indicating that names assigned to male genitalia align not only with the colonial construction of sexual racism but also with patriarchal gender relations. The article concludes by suggesting that names assigned to the black penis embody inherent contradictions that are not only characteristic of Southern African masculinities but also significantly complicate the dichotomy between 'self' and 'other', or 'us' and 'them', in contemporary Southern Africa.